Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1070/rc1987v056n05abeh003282
|View full text |Cite
|
Sign up to set email alerts
|

Activation and Catalytic Reactions of Alkanes in Solutions of Metal Complexes

Abstract: The reactions of saturated hydrocarbons and compounds modelling them with metal complexes, leading to the cleavage of the C-H and C-C bonds, are examined. In particular, processes which result in the formation of organometallic derivatives are described and the mechanism of the oxidation of alkanes by enzymes and their chemical models is discussed. The bibliography includes 355 references.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(58 citation statements)
references
References 37 publications
0
53
0
5
Order By: Relevance
“…Unlike the Mn I complex, there is a noticeable impact calculated for the spin-conserved barriers. For the O-atom insertion from low-spin Fe II to the low-spin transition state, 1 MCI → 1 OMBV transition state, the calculated ΔG ⧧ is ∼21 kcal/mol, which is ∼8 kcal/mol lower than for the quintet ground state converting to the low-spin transition state. In contrast, the conversion of a quintet ground state to a quintet transition state occurs with a much larger calculated ΔG ⧧ of ∼46 kcal/mol.…”
Section: ■ Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Unlike the Mn I complex, there is a noticeable impact calculated for the spin-conserved barriers. For the O-atom insertion from low-spin Fe II to the low-spin transition state, 1 MCI → 1 OMBV transition state, the calculated ΔG ⧧ is ∼21 kcal/mol, which is ∼8 kcal/mol lower than for the quintet ground state converting to the low-spin transition state. In contrast, the conversion of a quintet ground state to a quintet transition state occurs with a much larger calculated ΔG ⧧ of ∼46 kcal/mol.…”
Section: ■ Discussionmentioning
confidence: 99%
“…23,24 Among the more promising catalysts for hydrocarbon partial oxidation are electrophilic late transition metal systems. [1][2][3]9,14,15 For example, heating aqueous solutions of Pt II salts with hydrocarbons and an external oxidant produces alcohol or alkyl chloride compounds (the Shilov system). 1,12,25 The most commonly invoked pathway for Shilov catalysts involves initial alkane C−H activation to generate a Pt II −alkyl intermediate, oxidation of the Pt II −alkyl to produce a Pt IV −alkyl species, nucleophilic attack by water or chloride on the hydrocarbyl ligand, and dissociation of the functionalized product.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such systems, catalysed by heme-dependent monooxygenase P450 enzymes, the cofactor (NADPH) is required to donate two electrons to activate oxygen in order to generate a [(Porphyrin) + Fe IV = O] intermediate which attacks the C-H bonds (Scheme 2) [83]. Feng et al also showed selective oxidation of ethane to ethanol exclusively, with H 2 O 2 and NADH with higher turnover frequencies of up to 4692 h´1 at an NADH oxidation rate of 44,460 h´1 reported [65,83]. The catalytic cycle proposed for P450 catalysed alkane oxidation with O 2 is shown in Scheme 2.…”
Section: Enzymatic Approachesmentioning
confidence: 99%
“…Whilst a number of homogeneous catalytic systems have been reported for the activation of methane, the catalytic oxidation of ethane using homogeneous catalysts has rarely been studied [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65].…”
Section: Homogeneous Catalytic Approachesmentioning
confidence: 99%